Tinggalan Arkeologi Kalumpang untuk Edukasi dan Peluang Pengembangan Seni Kriya - Anggraeni, Anggraeni; Sektiadi, Sektiadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
Kalumpang is one of the important regions for archaeology related to the existence of Neolithic and the Early Metal Age settlement remains. The finds provide knowledge about the history of early habitation of the Indonesian Archipelago by the Austronesian speaking people. One of the important finds from three prehistoric sites in the Kalumpang area, namely the Minanga Sipakko, Kamassi, and Palemba sites, is potsherds with various decorations. Pottery is still survives today in the Kalumpang area, although its production is only based on consumer demand. On the contrary, handwoven production tend to increase significantly. Considering that pottery has played an important role in daily lives and rituals since the Prehistoric Period, this cultural heritage needs to be preserved. So far, there is no one who are interested in finding strategies to increase pottery production and attract the public's attention. Therefore, the team of research and Community Service from Archaeology Department Universitas Gadjah Mada need to identify: (1) the types of pottery that are still being produced by potters in the Kalumpang area; (2) early Neolithic-Metallic pottery decorative motif elements that can be applied to Kalumpang pottery that is still being produced; (3) new types of products related to the production of Kalumpang pottery. The results of identification are then set forth in the pottery motif design development module. This module can be used by various parties as an initial reference for developing pottery products. Agents of change, such as teachers and members of Karangtaruna, are expected to be able to use the modules to inspire traditional potters to continue their production by utilizing local cultural heritage. It is hoped that the production of Kalumpang pottery will be sustained and open up insight and concern for the wider community towards the cultural wealth of their ancestors. ==== Kalumpang merupakan salah satu wilayah penting dalam kajian arkeologi terkait adanya temuan sisa permukiman Neolitik dan Masa Logam Awal yang dapat memberikan sumbangan pengetahuan tentang sejarah penghunian Kepulauan Indonesia oleh penutur bahasa Melayu Polinesia (rumpun bahasa Austronesia). Salah satu temuan penting dari tiga situs Prasejarah di wilayah Kalumpang ialah Situs Minanga Sipakko, Kamassi, dan Palemba, yaitu fragmen tembikar dengan berbagai ragam hias. Di wilayah tersebut, tembikar masih diproduksi, tetapi hanya bila ada pemesan. Hal ini berbanding terbalik dengan produksi tenun yang cenderung meningkat secara signifikan. Mengingat tembikar sejak Masa Prasejarah menjadi barang penting dalam kehidupan sehari-hari dan ritual serta masih ada pembuatnya, warisan budaya ini perlu dilestarikan. Sejauh ini, belum ada pihak yang peduli dan berminat untuk mencari strategi agar produksi tembikar kembali meningkat dan diminati masyarakat luas. Oleh karena itu, Tim Penelitian-Pengabdian kepada Masyarakat Arkeologi UGM melakukan identifikasi terhadap: (1) jenis tembikar yang masih diproduksi oleh perajin di wilayah Kalumpang; (2) elemen motif hias tembikar Masa Neolitik-Logam Awal yang dapat diterapkan pada tembikar yang masih diproduksi; (3) bentuk produk baru terkait dengan produksi tembikar Kalumpang. Hasil identifikasi tersebut selanjutnya dituangkan dalam modul pengembangan desain motif tembikar. Modul tersebut dapat dipakai oleh berbagi pihak sebagai acuan awal untuk melakukan pengembangan produk tembikar. Agen perubahan, seperti guru dan anggota Karangtaruna, diharapkan dapat menggunakan modul tersebut untuk menginspirasi para perajin tembikar tradisional agar tetap berproduksi dengan memanfaatkan warisan budaya setempat. Dengan demikian, diharapkan produksi tembikar Kalumpang tetap lestari dan membuka wawasan serta kepedulian masyarakat luas terhadap kekayaan budaya nenek moyang.